Adaptive Recommendations for Enhanced Non‐linear Exploration of Annotated 3D Objects. (June 2015) - Rodriguez, M. Balsa; Agus, M.; Marton, F.; Gobbetti, E.
Abstract We introduce a novel approach for letting casual viewers explore detailed 3D models integrated with structured spatially associated descriptive information organized in a graph. Each node associates a subset of the 3D surface seen from a particular viewpoint to the related descriptive annotation, together with its author‐defined importance. Graph edges describe, instead, the strength of the dependency relation between information nodes, allowing content authors to describe the preferred order of presentation of information. At run‐time, users navigate inside the 3D scene using a camera controller, while adaptively receiving unobtrusive guidance towards interesting viewpoints and history‐ and location‐dependent suggestions on important information, which is adaptively presented using 2D overlays displayed over the 3D scene. The capabilities of our approach are demonstrated in a real‐world cultural heritage application involving the public presentation of sculptural complex on a large projection‐based display. A user study has been performed in order to validate our approach.